HIV serostatus, viral load, and midtrimester cervical length in a Zambian prenatal cohort. Issue 2 (29th April 2019) - Price, Joan T.; Vwalika, Bellington; Winston, Jennifer; Kumwenda, Andrew; Lubeya, Mwansa K.; Rittenhouse, Katelyn J.; Stringer, Elizabeth; Kasaro, Margaret P.; Stringer, Jeffrey S.A.
Abstract: Objective: To evaluate whether maternal HIV serostatus and plasma viral load (VL) are associated with midtrimester cervical length (CL). Methods: The Zambian Preterm Birth Prevention Study (ZAPPS) is an ongoing prospective cohort that began enrolling in Lusaka in August 2015. Pregnant women undergo ultrasound to determine gestational age and return for CL measurement at 16–28 weeks. We evaluated crude and adjusted associations between dichotomous indicators and short cervix (≤2.5 cm) via logistic regression, and between VL and CL as a continuous variable via linear regression. Results: This analysis includes 1171 women enrolled between August 2015 and September 2017. Of 294 (25.1%) HIV‐positive women, 275 (93.5%) had viral load performed close to CL measurement; of these, 148 (53.8%) had undetectable virus. Median CL was 3.6 cm (IQR 3.5–4.0) and was similar in HIV‐infected (3.7 cm, IQR 3.5–4.0) versus uninfected (3.6 cm, IQR 3.5–4.0) participants ( P =0.273). The odds of short CL were similar by HIV serostatus (OR 0.64; P =0.298) and detectable VL among those infected (OR 2.37, P =0.323). We observed no association between log VL and CL via linear regression (–0.12 cm; P =0.732). Conclusion: We found no evidence of association between HIV infection and short CL. Abstract : HIV serostatus and viral load were not associated with midtrimester short cervix in a Zambian obstetric cohort.